Assessment the Complications of Caesarean Section among Women’s attending AL -Diwaniyah Maternity and Pediatric Hospital/Iraq - Ghufran Fadhil Abo-Khuwait; Najmah Mahmood Meran (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aims: This study aimed to assess complications of caesarean section among pregnant women attending ALDiwaniyah Maternity and Pediatric Hospital; and find out relationship between complications of caesareansection and socio-demographic data of women.Methods: A descriptive cross-sectional study design is conducted for the period of December 26th 2020 toJune 1st 2021. The validity of the questionnaire is determine through a panel of experts and reliability wasachieved through a pilot study. By a purposive sample is selected among pregnant women who undergocaesarean section, data was collected through the use of questionnaire and interview techniques; andanalyzed through the descriptive and inferential statistic.Results: Findings indicate participants age, the mean age was 29±7.723, the age 20-29 years old (n=217;43.4%), a not read and write (n=149; 29.8%), more than half of studied participants were housewife(n=339; 67.8%), most of study participants were overweight (n=248; 49.6%). Findings showed that thefactors associated with caesarean section were post-partum hemorrhage, prolonged operation woundinfection and postpartum infection among studied sample. Regarding fetal complication ,Low Apgarscore(n=348;69.6%),respiratory distress syndrome (n=352;70.4%), and perinatal asphyxia(n=468;93.6%),among studied sample. The education and BMI have been significant relationship with their associatedfactors of caesarean section at p-value <0.05.